Kandungan Hara N, P, K pada Gawangan dan Jalan Panen Perkebunan Kelapa Sawit - Ismi Nuryenti; Dwi Probowati Sulistyani; Siti Masreah Bernas (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Nuryenti, et al.Â Content of Hara N, P, K on Gawangan and Harvest Road Oil Palm Plantation. JLSO 5(2):219-224.Â Differences in the location of oil palm plantations cause differences in nutrient content contained in the soil. This study aims to analyze the nutrient content of N, P, K of soil on gawangan and harvest road in PT. Sawit Mas Sejahtera. The method used is a detailed survey method with an observed area of 3 ha. Soil analysis results in nutrient content of N, P, K on harvest road showed higher yield compared to gawangan. N-total value on gawangan 0.11% and 0.16% Â harvest road, P-bray value on gawangan 6.15 ppm and 15 ppm harvest road, K-dd value on gawangan 0.10 me/100 g and 0.41 me/100 g harvest road. Soil pH on harvest road and gawangan is a very low pH soil ranging from 3.84 to 4.22. Palm oil production may increase by adding calcification first before the application of N, P, K fertilizer especially on harvest road to improve soil fertility and produce optimal production.